PENGGUNAAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Sopiani; Ricka Tesi Muskania (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes of students caused by the implementation of less innovative learning models. The purpose of this study was to analyze the effect of the TGT learning model on improving student learning outcomes in the Natural Sciences (IPA) subject of ecosystem material in class V of SD Negeri 06 Pontianak Timur. The study used a quantitative approach with a Classroom Action Research (CAR) design consisting of two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. The research sample was 28 class V A students consisting of 15 girls and 13 boys. Data collection was carried out through structured observation, tests (pretest and posttest), and documentation. Data were analyzed using descriptive statistics to determine the percentage of learning outcome completion. The results of the study showed a significant increase in learning outcomes, marked by completeness in the pretest cycle 1 of 0% to 3.57% in the pretest cycle 2. In the posttest cycle 1, student completeness reached 46.42% and increased to 75% in the posttest cycle 2. The average posttest score also increased from 70.35 in cycle 1 to 82.50 in cycle 2. These findings indicate that the TGT learning model is effective in improving science learning outcomes in Elementary Schools.